Alkali-labile sites in daughter DNA of damaged Escherichia coli do not reflect apyrimidinic sites - Slezáriková, V (Folia microbiologica, 1991)
Apyrimidinic sites arising after excision of uracil incorporated into DNA daughter strands might constitute alkali-labile sites. The hypothesis was checked in the present paper and the data obtained do not support it.
Keywords: Escherichia coli; vazebná místa; DNA Replication; Nucleic Acid Denaturation; replikace DNA; Binding Sites; ultrafialové záření; DNA Damage; denaturace nukleových kyselin; DNA bakterií; pyrimidiny; poškození DNA; alkálie; Pyrimidines; Alkalies; Ultraviolet Rays; DNA, Bacterial